Comparison of the Efficacy of Metacognition on Students’ Academic Performance Between Usa, France, Australia, and China - Tchounwou, Martha; Okoye, Ebele. C.; Iseguede, Faith (Advances in Social Sciences Research Journal, 2023)
pPrior research has emphasized the importance of metacognition as a contributing factor to increasing student retention at colleges and universities. Enhancing students' awareness of their cognitive skills is just as crucial. As students transition from a frequently controlled and encouraging high school setting to an uncontrolled university or college environment where they are expected to become extremely self-directed and autonomous, it is crucial that they quickly develop the skills and insights needed to become independent learners. However, many college students are ill-equipped to deal with the difficulties and challenges their academic environment presents, affecting their metacognitive skills. Metacognition is the capacity to track and manage thoughts and learning. This research reviewed and compared metacognition studies conducted on students in Australia, China, France, and the USA. These studies used self-regulated learning, self-efficacy, and meta-learning factors to evaluate metacognition performance among undergraduate students, including 362 participants in the USA, 128 in Australia, 118 in France, and 517 in China. Results revealed a positive impact of metacognition skills on all students, increasing their academic performance. However, compared to the participants in China, the results revealed that the overall effect size of self-regulated learning on academic achievement in the USA, France, and Australia was small because the Chinese students learned those metacognition habits at a very young age. The results also indicated that their beliefs contributed significantly to learning outcomes./p